STRATEGI DAKWAH MENGGUNAKAN MEDIA UNTUK PEMBANGUNAN: SUATU ANALISIS KONSEPTUAL - adeni - adeni (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2020)
This article aims to analyze some concepts of the approach of da’wah strategy activities in media relating to community development. By using the qualitative literature approach, three strategic approaches can be affirmed. First, the information (tabligh) approach. This approach sees that the determination of receiving information in media is centered on the message recipient. Preachers must not force their audiences to accept or reject the message. Second, the social change (taghyir) approach. Preachers in media must pay attention that the biggest change comes from the recipient's self-awareness, not by the desires of the sender of the message. Third, the development (ityan wa tankir) approach. Preachers in media must see society as a creative and innovative entity. A creative and independent society can choose which information is good for themselves for development. These three steps are oriented to form an independent society which is divided into two, namely civil community-khairiyat al-ummah which starts from the private, public, market, to state, by promoting the value of faith and morals. While the opponents are civil society-takwin al-ummah, the process of which is carried out from the state, market, public, to family. Artikel ini bertujuan menganalisis konsep strategi pendekatan yang tepat dalam kegiatan dakwan di media berkaitan dengan pembangunan masyarakat. Dengan pendekatan kualitatif kepustakaan dapat ditegaskan tiga strategi pendekatan, yaitu pertama, pendekatan informasi/tabigh. Pendekatan ini melihat bahwa penentuan penerimaan informasi di media berpusat pada penerima pesan. Pendakwah tidak boleh memaksa audiens untuk menerima atau menolak pesan. Kedua, pendekatan social change/taghyir, yang berarti perubahan. Pendakwah di media harus memperhatikan bahwa perubahan terbesar berasal dari kesadaran diri penerima, bukan oleh keinginan pengirim pesan/pendakwah. Ketiga, pendekatan development/ityan wa tankir, yang berarti perkembangan/pengembangan. Pendakwah di media harus melihat masyarakat sebagai entitas yang kreatif dan inovatif. Masyarakat yang kreatif dan mandiri bisa memilih mana informasi yang baik bagi dirinya untuk perkembangan. Tiga langkah ini diorientasikan untuk membentuk masyarakat mandiri yang terbagi menjadi dua, yaitu civil community-khairiyat al-ummah yang dimulai dari private, publik, pasar, hingga negara, dengan mengedepankan nilai iman dan akhlak. Sementara lawannya adalah civil society-takwin al-ummah, yang prosesnya dilakukan dari negara, pasar, publik, dan terakhir keluarga.